Carbon material, preparation method therefor, and use thereof

CN122455742BActive Publication Date: 2026-10-09LANXI ZHIDE ADVANCED MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610913700.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-09
Estimated Expiration
2046-06-24

AI Technical Summary

Technical Problem

该方案虽然实现了外密内疏的结构,但其表层的厚度难以控制,且其制备工艺涉及复杂的表面改性、微流控设备和双重模板去除步骤,工艺链条较长且成本较高

Benefits of technology

[0011]与现有技术相比,上述技术方案之一或多个技术方案能达到至少以下有益效果之一:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122455742B_ABST
    Figure CN122455742B_ABST
Patent Text Reader

Abstract

The application discloses a kind of carbon materials and its preparation method, application, belong to negative electrode material technical field.The carbon material is spherical particle, spherical particle is in turn from inside to outside loose core and dense shell;The radial thickness of the dense shell is D1, the radius of spherical particle is R1, D1 / R1 is 0.05~0.5;The average pore size of the loose core is greater than the average pore size of the dense shell, the average pore size of the loose core is 10~50nm;The average pore size of the dense shell is less than 10nm.The inside of carbon material is designed as loose carbon skeleton by the application, which provides sufficient physical buffer space for the volume expansion of silicon nanoparticles during charging and discharging process;At the same time, the surface layer of dense carbon layer with a radius of 5~50% is used as a "rigid shell", which effectively limits the stress transmission from internal expansion to outside, avoiding the overall particle breakage or electrode cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of negative electrode material technology, specifically relating to a carbon material and its preparation method and application. Background Technology

[0002] With the rapid development of electric vehicles and portable electronic devices, the market has placed higher demands on the energy density of lithium-ion batteries. The theoretical specific capacity of traditional graphite anodes (372 mAh / g) is nearing its limit and cannot meet the ever-increasing demand. Silicon, due to its ultra-high theoretical specific capacity (approximately 3579 mAh / g), is considered one of the most promising next-generation anode materials. However, silicon-based materials experience dramatic volume expansion (up to 300% or more) during charge and discharge, which leads to electrode material pulverization, repeated rupture and regeneration of the solid electrolyte interface film, resulting in a sharp decline in cycle life and low coulombic efficiency, severely restricting the commercial application of silicon-based anodes.

[0003] To address these issues, researchers have proposed a strategy of combining silicon with carbon materials. Carbon materials not only serve as a conductive framework for silicon particles, but their internal porous structure also provides a physical buffer for the volume expansion of silicon. For example, existing technologies have prepared carbon materials using template or activation methods and used them as substrates for silane deposition. However, current carbon material designs often prioritize high overall porosity. While this mitigates expansion, it frequently leads to a decrease in the overall mechanical strength of the material. Furthermore, excessive openings on the outer surface allow the electrolyte to directly contact the internal silicon particles, resulting in increased side reactions and a reduced first-coulombic efficiency.

[0004] To address this, the design of carbon materials with gradient structures has recently emerged. For example, patent CN121757843A discloses a method that utilizes the difference in hydrophilicity and hydrophobicity to distribute SiO2 templates and NH4Cl pore-forming agents inside microspheres, and prepares carbon materials with dense surface micropores and porous interiors via microfluidic emulsification. While this approach achieves a dense outer and porous inner structure, the thickness of the surface layer is difficult to control, and its preparation process involves complex surface modification, microfluidic equipment, and dual template removal steps, resulting in a long process chain and high cost. Summary of the Invention

[0005] To address the above problems, the purpose of this invention is to provide a carbon material, its preparation method, and its applications.

[0006] In a first aspect, the present invention provides a carbon material, wherein the carbon material is a spherical particle, and the spherical particle consists of a loose core and a dense shell from the inside out; the radial thickness of the dense shell is D1, the radius of the spherical particle is R1, and D1 / R1 is 0.05~0.5; the average pore size of the loose core is larger than the average pore size of the dense shell; the average pore size of the loose core is 10~50 nm; and the average pore size of the dense shell is less than 10 nm.

[0007] Secondly, the present invention provides a method for preparing a carbon material, comprising the following steps: S1. Preparation of oil and aqueous phases: The resin monomer, catalyst and additives are mixed evenly to obtain the oil phase; the dispersant and water are mixed evenly to obtain the aqueous phase; S2. Suspension preparation: At a set rotation speed, the oil phase is added dropwise to the aqueous phase, and the temperature is raised to the reaction temperature to carry out suspension emulsion polymerization, thereby obtaining a suspension containing prepolymerized microspheres; S3. Precursor synthesis: The suspension containing prepolymerized microspheres is subjected to wave solidification, and the precursor is obtained after solid-liquid separation; wherein: the wave solidification process is as follows: solidify at 80~150℃ for 1~5 min, and then solidify at 20~50℃ for 1~5 min; the wave solidification process is repeated 5~65 times. S4. Preparation of carbon materials: The precursor is carbonized and then activated in an atmosphere containing an activating gas to obtain the carbon material.

[0008] Thirdly, the present invention provides a silicon-carbon material, comprising a carbon material and silicon particles deposited in and / or on the surface of the carbon material pores; the carbon material is the aforementioned carbon material, or a carbon material prepared by the aforementioned method; the silicon particles are obtained by chemical vapor deposition of a silicon-containing precursor on the carbon material.

[0009] Fourthly, the present invention provides a negative electrode comprising a negative electrode active material, wherein the negative electrode active material comprises the silicon-carbon material described above.

[0010] Fifthly, the present invention provides a battery comprising the aforementioned negative electrode.

[0011] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: (1) This invention designs the internal structure of the carbon material as a loose carbon skeleton, providing sufficient physical buffer space for the volume expansion of silicon nanoparticles during charging and discharging; at the same time, it uses a dense surface region accounting for 5-50% of the radius as a "rigid shell", effectively limiting the stress transmission from the internal expansion to the outside, and avoiding the overall breakage of the particles or the cracking of the electrodes. Compared with a completely loose structure (easy to be pulverized as a whole) or a completely dense structure (no buffer space), the "hard outside and hollow inside" gradient structure of this invention can maintain extremely high structural integrity during cycling.

[0012] (2) By controlling the surface layer thickness to be more than 5% of the particle radius, this invention ensures the continuity of the dense carbon layer on the surface. This dense region can effectively improve the strength of the carbon material matrix and avoid the breakage of carbon material particles caused by the expansion of internal silicon particles, thereby making the battery exhibit better long-term cycle stability. In addition, the dense surface layer is conducive to the formation of a continuous conductive network, reducing the contact resistance between particles. By controlling the surface layer thickness to not exceed 50% of the radius, ion transport lag caused by excessive shell thickness is avoided.

[0013] (3) In this invention, thanks to the large pore structure of the internal three-dimensional interconnected loose framework, it can provide far more loading sites for silane deposition or nano-silicon filling than traditional carbon materials. At the same time, the external dense carbon layer ensures that even if the internal silicon content is increased, the overall mechanical strength and interface stability of the particles will not deteriorate. Therefore, this invention can achieve a silicon loading of no less than that of conventional silicon-carbon materials, thereby significantly improving the overall specific capacity of the anode material and meeting the design requirements of high-energy-density lithium-ion batteries. Attached Figure Description

[0014] Figure 1 The image shows a cross-sectional SEM image of the carbon material prepared in Example 1.

[0015] Figure 2 The image shows a cross-sectional SEM image of the carbon material prepared in Comparative Example 1. Detailed Implementation

[0016] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.

[0017] As mentioned above, in a first aspect, the present invention provides a carbon material, wherein the carbon material is a spherical particle, and the spherical particle consists of a loose core and a dense shell from the inside out; the radial thickness of the dense shell is D1, the radius of the spherical particle is R1, and D1 / R1 is 0.05~0.5, including but not limited to: 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, etc., preferably 0.05~0.2; the average pore size of the loose core is larger than the average pore size of the dense shell, the average pore size of the loose core is 10~50 nm; and the average pore size of the dense shell is less than 10 nm.

[0018] This invention provides a spherical carbon material with a dense outer layer and a porous inner layer, controlling the thickness of the dense surface region to be 5-50% of the particle radius. First, the porous inner core provides ample buffer space for silicon volume expansion, while the dense outer shell effectively restricts the outward transmission of expansion stress, ensuring structural integrity during cycling. Second, the dense outer shell acts as a fast electron channel, and the internal three-dimensional interconnected channels facilitate ion transport; together, they construct a highly efficient dual conductive network, improving the material's rate performance. Finally, the porous inner region can load a higher content of nano-silicon, achieving a higher specific capacity. Therefore, this invention achieves comprehensive improvements in structural stability, interface stability, rate performance, and energy density.

[0019] In some embodiments, after the spherical particle is cut radially, the cross-section consists of a loose core and a dense shell from the inside out. The cross-section is observed with a scanning electron microscope, and the interface where the carbon skeleton changes from a dense structure without obvious pores to a loose porous structure is used as the boundary between the loose core and the dense shell.

[0020] In some embodiments, within the region of the loose core, there are pores with a diameter of 10~50nm in any circular region with a diameter of 0.1D0, where D0 is the equivalent diameter of the spherical particle.

[0021] In some embodiments, the pore volume of the carbon material is 0.2~1.5 cm³. 3 / g, including but not limited to: 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, etc., preferably 0.5~1.2 cm3 / g.

[0022] In some embodiments, the median particle size of the carbon material is 2~30μm, including but not limited to: 2μm, 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 25μm, 30μm, etc., preferably 2~10μm.

[0023] In some embodiments, the particle size distribution of the carbon material is 0.2 to 1.5, including but not limited to: 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, etc., preferably 0.2 to 1.0.

[0024] Secondly, the present invention provides a method for preparing a carbon material, comprising the following steps: S1. Preparation of oil and aqueous phases: The resin monomer, catalyst and additives are mixed evenly to obtain the oil phase; the dispersant and water are mixed evenly to obtain the aqueous phase. S2. Suspension preparation: At a set rotation speed, the oil phase is added dropwise to the aqueous phase, and the temperature is raised to the reaction temperature to carry out suspension emulsion polymerization, thereby obtaining a suspension containing prepolymerized microspheres; S3. Precursor synthesis: The suspension described in S2 is subjected to wave solidification, and the precursor is obtained after solid-liquid separation; wherein: the wave solidification process is as follows: solidify at 80~150℃ for 1~5 min, and then solidify at 20~50℃ for 1~5 min; the wave solidification process is repeated 5~65 times. S4. Preparation of carbon materials: The precursor described in S3 is carbonized and then activated in an atmosphere containing an activating gas to obtain carbon materials.

[0025] The carbon material preparation method provided by this invention first obtains prepolymerized microspheres through suspension emulsion polymerization, and then employs a fluctuating curing process of alternating cycles of "high temperature for short time + low temperature maintenance" to achieve precise control of the radial crosslinking degree of the microspheres. The mechanism is as follows: In the high-temperature stage (80~150℃), the surface of the microspheres preferentially and rapidly crosslinks due to direct contact with the heat source, forming a dense thin layer; while the internal temperature has not yet risen due to the lag in heat conduction, and the degree of crosslinking reaction is very low. The subsequent low-temperature stage (20~50℃) rapidly brings the internal and external temperatures to a uniform level, and the crosslinking reaction slows down or essentially stops. Upon reheating, the already dense surface layer thickens further, while the internal crosslinking degree remains low. Through multiple cycles, a gradient structure of "highly crosslinked surface and lowly crosslinked internal layer" is gradually constructed. The preparation process of this invention does not require the addition of any template agent or pore-forming agent; the thickness of the dense surface region (accounting for 5~50% of the particle radius) can be precisely controlled simply by adjusting the curing temperature and the number of cycles. The process is simple, low-cost, and suitable for industrial scale-up. Highly cross-linked polymers tend to form denser, microporous carbon structures during carbonization; while regions with low cross-linking degrees have loosely arranged molecular chains, releasing more volatile small molecules during carbonization, making it easier to form interconnected, loose structures, achieving a gradient pore structure of "dense on the outside and sparse on the inside". This method avoids the damage to the material structure caused by traditional post-processing pore-forming, is highly compatible with existing resin-based carbon material preparation processes, and has strong practicality and promotional value.

[0026] In some embodiments, in step S1, the resin monomer is one of phenolic resin monomer, urea-formaldehyde resin monomer, epoxy resin monomer, and styrene.

[0027] In some embodiments, in step S1, the catalyst is one of hydrochloric acid, oxalic acid, sodium hydroxide, ammonia, ammonium chloride, formic acid, phosphoric acid, triethylamine, benzyl dimethylamine, benzoyl peroxide, and azobisisobutyronitrile.

[0028] In some embodiments, in step S1, the auxiliary agent is one or more of hexamethylenetetramine, toluene, n-heptane, ethylenediamine, diethylenetriamine, polyamide, divinylbenzene, and melamine.

[0029] In some embodiments, in step S1, the dispersant is one or more of polyvinyl alcohol, gelatin, sodium carboxymethyl cellulose, sodium dodecyl sulfonate, hydroxyethyl cellulose, and calcium phosphate.

[0030] For different resin systems, specific resin monomers, catalysts, dispersants, and additives, as well as their dosage ratios, were further optimized, as follows: In step S1, when the resin is a phenolic resin, the resin monomers include phenolic monomers and aldehyde monomers. The phenolic monomers are one or more of phenol, cresol, bisphenol A, and resorcinol; the aldehyde monomers are one or more of formaldehyde, acetaldehyde, glyoxal, and furfural; the catalyst is one of hydrochloric acid, oxalic acid, sodium hydroxide, and ammonia water; the dispersant is one or more of polyvinyl alcohol, gelatin, and sodium carboxymethyl cellulose; the additives include a curing agent and a pore-forming agent. The curing agent is hexamethylenetetramine; the pore-forming agent is one or two of toluene and n-heptane. The molar ratio of phenolic monomers to aldehyde monomers is (0.5~0.9):1; the amount of catalyst added is 0.1~2% of the total mass of resin monomers; the amount of pore-forming agent added is 1~20% of the total mass of resin monomers; the amount of curing agent added is 1~10% of the total mass of resin monomers; the mass of dispersant is 5~30% of the total mass of resin monomers; and the volume ratio of oil phase to water phase is 1:(2~10).

[0031] In step S1, when the resin is urea-formaldehyde resin, the resin monomers include urea and aldehyde monomers; the aldehyde monomers are one or more of formaldehyde, acetaldehyde, glyoxal, and furfural; the catalyst is one or more of ammonium chloride, formic acid, and phosphoric acid; the dispersant is one or two of polyvinyl alcohol and sodium dodecyl sulfonate; and the auxiliary agent is melamine. The molar ratio of urea to aldehyde monomers is (0.8~1.2):1; the amount of catalyst added is 0.2~3% of the total mass of resin monomers; the amount of auxiliary agent added is 2~15% of the total mass of resin monomers; the mass of dispersant is 5~30% of the total mass of resin monomers; and the volume ratio of oil phase to water phase is 1:(2~10).

[0032] In step S1, when the resin is epoxy resin, the resin monomer includes epoxy resin E-51; the catalyst is one or both of triethylamine and benzyl dimethylamine; the dispersant is one or both of polyvinyl alcohol and gelatin; and the auxiliary agent is one or more of ethylenediamine, diethylenetriamine, and polyamide. The amount of catalyst added is 0.3-2.5% of the total mass of the resin monomer; the amount of auxiliary agent added is 1-10% of the total mass of the resin monomer; the mass of the dispersant is 5-30% of the total mass of the resin monomer; and the volume ratio of the oil phase to the water phase is 1:(2-10).

[0033] In step S1, when the resin is polystyrene, the resin monomer is styrene; the catalyst is one or both of benzoyl peroxide and azobisisobutyronitrile; the dispersant is one or more of polyvinyl alcohol, hydroxyethyl cellulose, and calcium phosphate; and the additive is divinylbenzene. The amount of catalyst added is 0.5-5% of the total mass of the resin monomer; the amount of additive added is 1-10% of the total mass of the resin monomer; the mass of the dispersant is 5-30% of the total mass of the resin monomer; and the volume ratio of the oil phase to the aqueous phase is 1:(2-10).

[0034] In some embodiments, in step S2, the rotation speed is set to 100~800 rpm, including but not limited to: 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, etc.; the reaction temperature is set to 80~150℃, including but not limited to: 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, etc.; the suspension emulsion polymerization time is set to 20~120 min, including but not limited to: 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc., preferably 30~60 min.

[0035] In some embodiments, in step S3, the cyclic curing process is repeated 10 to 40 times.

[0036] In some embodiments, in step S4, the carbonization temperature is 500~800℃, including but not limited to: 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, etc.; the carbonization time is 1~4h, including but not limited to: 1h, 2h, 3h, 4h, etc.

[0037] In some embodiments, in step S4, the activating gas is one or both of water vapor and carbon dioxide, the activation temperature is 700~1000℃, including but not limited to: 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, etc., and the activation time is 2~10h, including but not limited to: 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.

[0038] Thirdly, the present invention provides a silicon-carbon material, comprising a carbon material and silicon particles deposited in and / or on the surface of the carbon material pores; wherein the carbon material is the aforementioned carbon material, or a carbon material prepared by the aforementioned method.

[0039] In some embodiments, the method for preparing the silicon-carbon material includes the following steps: placing the carbon material in a vapor deposition apparatus, introducing silicon source gas and carrier gas, performing vapor deposition, and obtaining the silicon-carbon material after the deposition is completed.

[0040] In some embodiments, the silicon source gas is one or more of SiH4, Si2H6, SiCl4, and SiHCl3, the carrier gas is nitrogen, and the volume ratio of silicon source gas to carrier gas is 1:(2~10), including but not limited to: 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.; the silane partial pressure in the reaction system is 1~5 kPa, including but not limited to: 1 kPa, 2 kPa, 3 kPa, 4 kPa, 5 kPa, etc.; the vapor deposition temperature is 450~600℃, including but not limited to: 450℃, 500℃, 550℃, 600℃, etc.; the vapor deposition time is 2~6h, including but not limited to: 2h, 3h, 4h, 5h, 6h, etc.

[0041] By controlling the partial pressure of silane, the pyrolysis rate can be slowed down, which is conducive to the diffusion and nucleation of silicon atoms into the pores of carbon materials and avoids them accumulating only on the surface. Controlling the partial pressure of silane can maintain the stability of the precursor concentration and prevent it from being carried away by the gas flow before it has fully reacted. The deposition temperature can ensure the effective pyrolysis of silane and protect the stability of the carbon material skeleton structure.

[0042] In some embodiments, the silicon nanoparticles are primarily loaded within a carbon material.

[0043] In some embodiments, the silicon nanoparticles are loaded onto a carbon matrix via chemical vapor deposition using silane.

[0044] Fourthly, the present invention provides a negative electrode comprising a negative electrode active material, wherein the negative electrode active material comprises the silicon-carbon material described above.

[0045] Fifthly, the present invention provides a battery comprising the aforementioned negative electrode.

[0046] Example 1 The method for preparing the carbon material in this embodiment is as follows: S1. Phenol, formaldehyde, hexamethylenetetramine, 37wt% hydrochloric acid, and toluene are mixed, wherein the molar ratio of phenol to formaldehyde is 0.7:1, the amount of hydrochloric acid added is 1% of the total mass of phenol and formaldehyde, the amount of hexamethylenetetramine added is 5% of the total mass of phenol and formaldehyde, and the amount of toluene added is 10% of the total mass of phenol and formaldehyde; an oil phase is obtained; PVA is added to deionized water to obtain an aqueous phase; the oil phase is added dropwise to the aqueous phase at a speed of 400 rpm, wherein the volume ratio of the oil phase to the aqueous phase is 1:5, and the mass of the dispersant is 17% of the total mass of phenol and formaldehyde; the temperature is raised to 95℃, and suspension emulsion polymerization is carried out for 40 min to obtain a reaction solution containing prepolymerized microspheres.

[0047] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked and cured in a 120°C water bath for 1 min, then quickly placed in a 50°C water bath for another 1 min of crosslinking and curing, and then the cyclic wave curing process is repeated 47 times (the total number of cycles is 48). After solid-liquid separation, phenolic resin microspheres are obtained.

[0048] S3. Phenolic resin microspheres were carbonized in a nitrogen atmosphere at 650°C for 2 hours, and then the temperature was raised to 750°C. Water vapor was used as the activation gas and nitrogen was used as the carrier (the volume ratio of water vapor to nitrogen was 10:90) for 4 hours to obtain carbon material.

[0049] The internal cross-section of the carbon material prepared in this embodiment, obtained by Ar ion polishing and slicing, was measured by SEM. The test results are shown below. Figure 1 It can be seen that the carbon material consists of spherical carbon particles that are dense on the outside and sparse on the inside; the surface of the particles is a dense carbon layer containing micropores, while the inside is a loose carbon skeleton containing macropores.

[0050] Preparation of silicon-carbon materials: The carbon material was placed in a fluidized bed reactor and heated from room temperature to 520℃ at a rate of 2℃ / min in a N2 atmosphere; then the mixture of 20 vol% SiH4 and 80 vol% N2 was introduced, and the silane partial pressure in the reaction system was controlled at 3 kPa for vapor deposition for 5 h; finally, the material was naturally cooled in a N2 atmosphere to obtain silicon-carbon materials; the silicon content in the silicon-carbon materials was 49.6 wt%.

[0051] Comparative Example 1 This is basically the same as Example 1, except that step S2 is different. The specific preparation method is as follows: S1, the same as step S1 in Example 1.

[0052] S2. The reaction solution containing the prepolymerized microspheres was crosslinked and cured in a water bath at 120°C for 96 min. After solid-liquid separation, phenolic resin microspheres were obtained. S3, the same as step S3 in Example 1.

[0053] The internal cross-section of the carbon material prepared in this comparative example was measured by SEM using Ar ion polishing and sectioning. The results are shown in the figure. Figure 2 It can be seen that the internal and surface pore structures are relatively dense, without a structure that is sparse inside and dense outside.

[0054] The preparation of silicon-carbon materials is the same as in Example 1.

[0055] Example 2 The method for preparing the carbon material in this embodiment is as follows: S1, the same as step S1 in Example 1.

[0056] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked and cured in a 120°C water bath for 2 minutes, then quickly placed in a 50°C water bath for another 2 minutes of crosslinking and curing, and then the cyclic wave curing process is repeated 23 times (the total number of cycles is 24). After solid-liquid separation, phenolic resin microspheres are obtained.

[0057] S3, same as step S3 in Example 1.

[0058] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 1.

[0059] Example 3 The method for preparing the carbon material in this embodiment is as follows: S1, the same as step S1 in Example 1.

[0060] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked and cured in a 120°C water bath for 3 minutes, then quickly placed in a 50°C water bath for another 3 minutes, and then the cyclic wave curing process is repeated 15 times (the total number of cycles is 16). After solid-liquid separation, phenolic resin microspheres are obtained.

[0061] S3, same as step S3 in Example 1.

[0062] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 1.

[0063] Example 4 The method for preparing the carbon material in this embodiment is as follows: S1, the same as step S1 in Example 1.

[0064] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked in a 120°C water bath for 4 min, then quickly placed in a 50°C water bath for another 4 min of crosslinking, and then the cyclic wave process is repeated 11 times (the total number of cycles is 12). After solid-liquid separation, phenolic resin microspheres are obtained.

[0065] S3, same as step S3 in Example 1.

[0066] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 1.

[0067] Example 5 The method for preparing the carbon material in this embodiment is as follows: S1, the same as step S1 in Example 1.

[0068] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked and cured in a 120°C water bath for 5 minutes, then quickly placed in a 50°C water bath for 5 minutes for crosslinking and curing, and then the cyclic wave curing process is continued for 9 times (the total number of cycles is 10 times). After solid-liquid separation, phenolic resin microspheres are obtained.

[0069] S3, same as step S3 in Example 1.

[0070] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 1.

[0071] Example 6 It is basically the same as Example 3, except that in step S1, the suspension emulsion polymerization time is 25 min.

[0072] S1. Phenol, formaldehyde, hexamethylenetetramine, 37wt% hydrochloric acid, and toluene are mixed, wherein the molar ratio of phenol to formaldehyde is 0.7:1, the amount of hydrochloric acid added is 1% of the total mass of phenol and formaldehyde, the amount of hexamethylenetetramine added is 5% of the total mass of phenol and formaldehyde, and the amount of toluene added is 10% of the total mass of phenol and formaldehyde; an oil phase is obtained; PVA is added to deionized water to obtain an aqueous phase; the oil phase is added dropwise to the aqueous phase at a speed of 400 rpm, wherein the volume ratio of the oil phase to the aqueous phase is 1:5, and the mass of the dispersant is 17% of the total mass of phenol and formaldehyde; the temperature is raised to 95℃, and suspension emulsion polymerization is carried out for 25 min to obtain a reaction solution containing prepolymerized microspheres.

[0073] S2 is basically the same as step S2 in Example 3, except that the total number of cycles is 18.

[0074] S3, same as step S3 in Example 3.

[0075] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 3.

[0076] Example 7 It is basically the same as Example 3, except that in step S1, the suspension emulsion polymerization time is 60 min.

[0077] S1. Phenol, formaldehyde, hexamethylenetetramine, 37wt% hydrochloric acid, and toluene are mixed, wherein the molar ratio of phenol to formaldehyde is 0.7:1, the amount of hydrochloric acid added is 1% of the total mass of phenol and formaldehyde, the amount of hexamethylenetetramine added is 5% of the total mass of phenol and formaldehyde, and the amount of toluene added is 10% of the total mass of phenol and formaldehyde; an oil phase is obtained; PVA is added to deionized water to obtain an aqueous phase; the oil phase is added dropwise to the aqueous phase at a speed of 400 rpm, wherein the volume ratio of the oil phase to the aqueous phase is 1:5, and the mass of the dispersant is 17% of the total mass of phenol and formaldehyde; the temperature is raised to 95℃, and suspension emulsion polymerization is carried out for 60 min to obtain a reaction solution containing prepolymerized microspheres.

[0078] S2 is basically the same as step S2 in Example 3, except that the total number of cycles is 13.

[0079] S3, same as step S3 in Example 3.

[0080] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 3.

[0081] Example 8 It is basically the same as Example 3, except that the crosslinking curing temperature is different in step S2.

[0082] S1, the same as step S1 in Example 3.

[0083] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked and cured in a 100°C water bath for 3 minutes, then quickly placed in a 40°C water bath for another 3 minutes of crosslinking and curing, and then the cyclic wave curing process is repeated 31 times (the total number of cycles is 32). After solid-liquid separation, phenolic resin microspheres are obtained.

[0084] S3, same as step S3 in Example 3.

[0085] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 3.

[0086] Example 9 It is basically the same as Example 3, except that the crosslinking curing temperature is different in step S2.

[0087] S1, the same as step S1 in Example 3.

[0088] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked and cured in a 150°C water bath for 3 minutes, then quickly placed in a 50°C water bath for another 3 minutes to continue crosslinking and curing, and then the cyclic wave curing process is repeated 7 times (the total number of cycles is 8 times). After solid-liquid separation, phenolic resin microspheres are obtained.

[0089] S3, same as step S3 in Example 3.

[0090] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 3.

[0091] Example 10 It is basically the same as Example 3, except that the crosslinking curing temperature is different in step S2.

[0092] S1, the same as step S1 in Example 3.

[0093] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked and cured in an 80°C water bath for 3 minutes, then quickly placed in a 20°C water bath for another 3 minutes to continue crosslinking and curing, and then the cyclic wave curing process is repeated 63 times (the total number of cycles is 64). After solid-liquid separation, phenolic resin microspheres are obtained.

[0094] S3, same as step S3 in Example 3.

[0095] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 3.

[0096] Comparative Example 2 It is basically the same as Example 3, except that the crosslinking curing time is different in step S2.

[0097] S1, the same as step S1 in Example 3.

[0098] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked and cured in a 120°C water bath for 0.5 min, then quickly placed in a 20°C water bath for another 0.5 min of crosslinking and curing, and then the cyclic wave curing process is repeated 71 times (the total number of cycles is 72). After solid-liquid separation, phenolic resin microspheres are obtained.

[0099] S3, same as step S3 in Example 3.

[0100] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 3.

[0101] Comparative Example 3 It is basically the same as Example 3, except that the crosslinking curing time is different in step S2.

[0102] S1, the same as step S1 in Example 3.

[0103] S2. The reaction solution containing prepolymerized microspheres is subjected to cyclic wave curing. The wave curing process is as follows: the reaction solution containing prepolymerized microspheres is crosslinked and cured in a 120°C water bath for 6 minutes, then quickly placed in a 20°C water bath for another 6 minutes of crosslinking and curing, and then the cyclic wave curing process is repeated 8 times (the total number of cycles is 9 times). After solid-liquid separation, phenolic resin microspheres are obtained.

[0104] S3, same as step S3 in Example 3.

[0105] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 3.

[0106] Comparative Example 4 It is basically the same as Example 3, except that in step S1, the suspension emulsion polymerization is carried out for 10 minutes.

[0107] S1. Phenol, formaldehyde, hexamethylenetetramine, 37wt% hydrochloric acid, and toluene are mixed, wherein the molar ratio of phenol to formaldehyde is 0.7:1, the amount of hydrochloric acid added is 1% of the total mass of phenol and formaldehyde, the amount of hexamethylenetetramine added is 5% of the total mass of phenol and formaldehyde, and the amount of toluene added is 10% of the total mass of phenol and formaldehyde; an oil phase is obtained; PVA is added to deionized water to obtain an aqueous phase; the oil phase is added dropwise to the aqueous phase at a speed of 400 rpm, wherein the volume ratio of the oil phase to the aqueous phase is 1:5, and the mass of the dispersant is 17% of the total mass of phenol and formaldehyde; the temperature is raised to 150℃, and suspension emulsion polymerization is carried out for 10 min to obtain a reaction solution containing prepolymerized microspheres.

[0108] S2 is basically the same as step S2 in Example 3, except that the total number of cycles is 24.

[0109] S3, same as step S3 in Example 3.

[0110] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 3.

[0111] Comparative Example 5 It is basically the same as Example 3, except that in step S1, the suspension emulsion polymerization time is 130 min.

[0112] S1. Phenol, formaldehyde, hexamethylenetetramine, 37wt% hydrochloric acid, and toluene are mixed, wherein the molar ratio of phenol to formaldehyde is 0.7:1, the amount of hydrochloric acid added is 1% of the total mass of phenol and formaldehyde, the amount of hexamethylenetetramine added is 5% of the total mass of phenol and formaldehyde, and the amount of toluene added is 10% of the total mass of phenol and formaldehyde; an oil phase is obtained; PVA is added to deionized water to obtain an aqueous phase; the oil phase is added dropwise to the aqueous phase at a speed of 400 rpm, wherein the volume ratio of the oil phase to the aqueous phase is 1:5, and the mass of the dispersant is 17% of the total mass of phenol and formaldehyde; the temperature is raised to 80℃, and suspension emulsion polymerization is carried out for 130 min to obtain a reaction solution containing prepolymerized microspheres.

[0113] S2 is basically the same as step S2 in Example 3, except that the total number of cycles is 10.

[0114] S3, same as step S3 in Example 3.

[0115] Preparation of silicon-carbon materials: Same as the preparation of silicon-carbon materials in Example 3.

[0116] The ratio D1 / R1 of the thickness D1 of the dense region in the carbon materials prepared in Examples 1-10 and Comparative Examples 1-5 to the radius R1 of the spherical carbon material particles was tested using SEM images. The loose skeleton region of the carbon material was magnified to 80,000 times using SEM, and the pore size of at least 100 pores was tested. The range of these pores is a part of the pore size of the loose core inside the carbon material.

[0117] The particle size and particle size distribution of carbon materials were tested using a laser particle size analyzer.

[0118] The pore volume of carbon materials was measured by static adsorption of N2, and the pore size range of the loose core and dense shell could be obtained by fitting and analyzing the data using the DFT method.

[0119] The test results are shown in Table 1.

[0120] Table 1 As can be seen from the data in Table 1, Examples 1-5 demonstrate that the surface thickness can be gradient-controlled by adjusting the number of cycles and the duration of each curing cycle in the fluctuating curing process. It should be noted that, given similar total high-temperature curing times (48 min, 48 min, 48 min, 48 min, and 50 min for Examples 1-5, respectively), fewer cycles mean a longer duration of each high-temperature curing cycle (gradually increasing from 1 min in Example 1 to 5 min in Example 5). The mechanism is as follows: a longer duration of each high-temperature curing cycle allows the microsphere surface to undergo more thorough thermal cross-linking during each high-temperature stage, resulting in a more significant increase in the thickness of the dense region per cycle, thus achieving a thicker surface layer with fewer cycles. Furthermore, more time is available for heat transfer into the particle interior during each high-temperature cycle, leading to a certain degree of cross-linking in the internal region as well. Consequently, the internal porous pore size formed after carbonization gradually decreases. Furthermore, the setting of the low-temperature stage is crucial: it effectively "freezes" the highly cross-linked structure already formed on the surface by rapidly reducing the system temperature, preventing it from homogenizing due to molecular chain rearrangement in the subsequent high-temperature stage; simultaneously, the low-temperature period allows internal heat to dissipate, avoiding excessive cross-linking caused by a continuous increase in internal temperature, thus maintaining the gradient difference of "dense on the outside and sparse on the inside". Therefore, in this invention, the radial thickness of the surface layer is not simply positively correlated with the number of cycles, but mainly depends on the duration of a single high-temperature curing cycle: as the curing time increases (i.e., the number of cycles decreases), the percentage of the radial thickness of the surface layer to the particle radius gradually increases, while the internal loose pore size gradually decreases due to the increased degree of internal cross-linking. By controlling this combination of parameters, the required outer shell thickness and core pore size can be precisely obtained, realizing the customized design of the gradient structure of carbon materials. Examples 6-10, while maintaining a basically stable surface thickness, achieved independent control of the internal loose pore size by adjusting the initial degree of curing or the cross-linking curing temperature of the prepolymerized microspheres. When the prepolymer curing degree is low, the number of cycles needs to be increased to achieve the same surface layer thickness; when the crosslinking temperature is low, the number of cycles also needs to be increased, and this affects the internal porous pore size. Comparative Example 1, without cyclic curing, forms a single dense zone; the single high-temperature curing time of Comparative Examples 2 and 3 is too short or too long, resulting in the D1 / R1 value of the dense layer exceeding the range; the suspension emulsion polymerization time of Comparative Examples 4 and 5 is too short or too long, resulting in the initial curing degree being too low or too high, resulting in the porous pore size exceeding the range.

[0121] Battery performance test: Using the silicon-carbon materials provided in Examples 1-10 and Comparative Examples 1-5 as the negative electrode active materials, negative electrode sheets were prepared respectively. CR2032 coin cells were fabricated using conventional methods, and the electrical performance of the cells was tested. The specific testing methods are as follows: 1. Half-cell preparation and electrochemical performance testing: (1) Half-cell assembly: Assemble CR2032 button cells in a glove box, with lithium metal sheet as counter electrode, negative electrode sheet as working electrode, polypropylene microporous membrane as separator, and LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC=1:1), wherein the concentration of LiPF6 is 1mol / L.

[0122] The battery was tested for charge and discharge using the LAND battery testing system.

[0123] (2) Cyclic specific capacity and initial efficiency test: After the CR2032 button cell was left to stand for 6 hours, it was discharged to 0.005V at 0.05C and then discharged to 0.005V at 0.01C; after standing for 5 minutes, it was charged to 0.8V at a constant current of 0.05C; the initial delithiation specific capacity at 0.8V is the specific capacity (or mass specific capacity) of the electrode material at 0.8V, and the ratio of the initial delithiation capacity at 0.8V to the initial lithium insertion capacity at 0.8V is the initial coulombic efficiency of the battery at 0.8V.

[0124] (3) Ratio testing method: After the coin cell batteries completed the cycle capacity and initial efficiency tests, they were subjected to the following charge-discharge cycles at the following rates: (1) Discharge to 0.005V at 0.1C and then charge to 1.5V at 0.1C. Repeat this cycle 3 times and record the discharge capacity and charge capacity each time. (2) Discharge to 0.005V at 0.1C and then charge to 1.5V at 1C. Repeat this cycle 3 times and record the discharge capacity and charge capacity each time. The 1C / 0.1C rate is obtained by dividing the 1C and 1.5V charge capacity of the third cycle by the 0.1C and 1.5V charge capacity of the third cycle.

[0125] 2. Full cell preparation and electrochemical performance testing: Using the silicon-based composite materials provided in Examples 1-10 and Comparative Examples 1-5 as the negative electrode active material, pouch cells containing the negative electrode active material were prepared using conventional methods, and their electrical performance was tested. The pouch cells were prepared in a dehumidified room at a dew point of -45°C. Charge-discharge cycle tests were performed on the cells using the LANBTS battery testing system. The specific test method is as follows: (1) Preparation of positive electrode sheet: The positive electrode active material LiCoO2, conductive agent SuperP, binder PVDF and solvent NMP are mixed evenly in a mass ratio of 92:3:5:150 and then evenly coated on the positive electrode current collector. Then, it is dried at 80℃ to obtain the positive electrode sheet.

[0126] (2) Preparation of negative electrode sheet: The negative electrode active material, conductive agent SuperP, binder polyacrylic acid and solvent deionized water are mixed evenly in a mass ratio of 95:1:4:120. The mixture is then evenly coated on the negative electrode current collector and dried at 100°C to obtain the negative electrode sheet.

[0127] (3) The positive and negative electrode sheets are stacked in a square and separated by a polypropylene separator to form a battery cell, which is then packaged into an aluminum-plastic bag. An electrolyte of the appropriate capacity is injected into the aluminum-plastic bag, and the bag is vacuum sealed to obtain a soft-pack battery. The electrolyte is a mixture of LiPF6 EC and DEC, wherein the concentration of LiPF6 is 1 mol / L and the volume ratio of EC to DEC is 1:1.

[0128] (4) Formation and Capacity Testing: After liquid injection and sealing, the battery begins formation. It is placed in a constant temperature chamber at 25°C for 12 hours, then charged at a constant current of 0.02C to 3.3V, placed for 30 minutes, charged at a constant current of 0.025C to 3.8V, placed for 10 minutes, and charged at a constant current of 0.33C to 4.2V. After formation, the battery is vacuum-sealed and the gas bag is removed. Then, capacity testing is performed. The battery is charged at a constant current of 0.33C to 4.45V, placed for 10 minutes, discharged at a constant current of 1C to 3V, placed for 10 minutes, and discharged at a constant current of 0.3C to 3V. The capacity testing is then completed. The ratio of the discharge capacity to the charge capacity during the formation and capacity testing of the pouch battery is the initial efficiency of the battery.

[0129] (5) 25℃ Cyclic Test: Place the battery in a 25℃ constant temperature chamber, charge it to 4.45V with a constant current of 1C, and then charge it to 0.1C with a constant voltage of 4.45V. After standing for 10 minutes, discharge it to 3.0V with a constant current of 1C and stand for 10 minutes. Repeat the above charging and discharging steps. Record the capacity retention rate after 500 cycles.

[0130] Table 2 As can be seen from the half-cell data in Table 2, the silicon-carbon material assembled from the carbon material prepared in Example 3 exhibits excellent specific capacity, initial efficiency, and rate performance. This may be because, in the "dense on the outside and sparse on the inside" structure of the gradient carbon material, the dense surface layer effectively improves the strength of the carbon material matrix, while the loose internal structure provides a buffer space for silicon expansion and ensures rapid ion transport.

[0131] The half-cell assembled from silicon-carbon materials prepared using the carbon materials of Comparative Example 1 (traditional non-gradient carbon materials) showed a significant decrease in initial efficiency and rate performance at 0.8V compared to Example 3. This may be because the completely dense pore structure causes more silicon to deposit outside the pores, and the excessively small pores restrict the nucleation and growth space of silicon atoms, making it easy for silicon to agglomerate at local sites to form large particles that cannot be uniformly dispersed, thus reducing the initial efficiency and rate performance of the battery.

[0132] The silicon-carbon half-cells assembled from carbon materials with thinner surface layers in Examples 1 and 2 exhibit better initial efficiency and rate performance at 0.8V than Comparative Example 1, but slightly lower than Example 3. This may be because, although the surface layer thickness is insufficient, it still possesses a certain degree of dense structure, which can improve the strength and electronic conductivity of the carbon material matrix. Furthermore, the internal porosity is conducive to the deposition of silicon particles and provides buffer space for the expansion of silicon particles, thus showing a significant improvement over Comparative Example 1, which lacks a gradient structure. However, compared to Example 3, which has a better surface layer thickness, the integrity and mechanical strength of its dense carbon layer are slightly weaker, making it more prone to microcracks, resulting in a slight decrease in initial efficiency and rate performance.

[0133] The silicon-carbon half-cells assembled from carbon materials with a thicker surface layer in Examples 4 and 5 showed better initial efficiency at 0.8V than Comparative Example 1, but slightly lower rate performance than Example 3. This may be because: the thicker, denser outer shell further increases strength, and the presence of certain porous areas allows for silicon particle deposition, thus significantly improving initial efficiency compared to Comparative Example 1 without a gradient structure; however, the excessively thick carbon layer prolongs the solid-phase diffusion path of lithium ions, leading to increased lithium-ion transport resistance and a decrease in rate performance.

[0134] Examples 6-7 (surface layer thickness approximately 23-24%) show silicon-carbon half-cells assembled from carbon materials. Both their initial efficiency (0.8V) and rate performance are superior to Comparative Example 1, with Example 6 approaching the level of Example 3. Compared to Comparative Example 1, both examples exhibit significantly better initial efficiency and rate performance. This is likely because, despite differences in pore size, both are sufficient for silicon particle deposition, and the suitable dense surface layer thickness effectively enhances strength, showing a significant improvement over the non-gradient carbon material of Comparative Example 1. Compared to Example 3, Example 6's overall performance is closest to Example 3, with both having pore sizes within the optimal pore size window for their porous cores. Example 7's rate performance is slightly lower than Example 3, possibly because the smaller pore size of the porous core somewhat limits ion transport.

[0135] The half-cells assembled from silicon-carbon materials prepared with carbon materials in Examples 8 (100℃ / 40℃), 9 (150℃ / 50℃), and 10 (80℃ / 20℃) have a first-efficiency and rate performance at 0.8V that are basically equivalent to those in Example 3.

[0136] As can be seen from the full-cell cycling data in Table 2, the full cell assembled from silicon-carbon materials prepared using the carbon materials in Comparative Example 1 (conventional non-gradient carbon materials) exhibits a significantly lower capacity retention rate after 500 cycles compared to Example 3. This may be because the completely dense pore structure causes more silicon to deposit outside the pores, making the silicon outside the pores prone to expansion and cracking, thus leading to a decrease in cycling performance.

[0137] The silicon-carbon full cells assembled from carbon materials with thinner surface layers in Examples 1 and 2 exhibit better capacity retention after 500 cycles than Comparative Example 1, but slightly lower than Example 3. This may be because the thinner surface layer provides some expansion constraint, mitigating structural damage, and the internal pores provide more space for silicon deposition, thus resulting in better cycle performance than Comparative Example 1. However, insufficient surface mechanical support leads to microcracks and structural damage under long-term cycling, resulting in a slightly lower cycle retention rate than the optimal structure in Example 3.

[0138] The silicon-carbon full cells assembled from carbon materials with a thicker surface layer in Examples 4 and 5 showed better capacity retention after 500 cycles than Comparative Example 1, but slightly lower than Example 3. This may be because the excessively thick surface layer compresses the internal buffer space, making it difficult to fully release the silicon expansion stress, while ion transport is hindered, resulting in a slightly faster capacity decay under long-term cycling.

[0139] The silicon-carbon full cells assembled from carbon materials in Examples 6 and 7 showed significantly better capacity retention after 500 cycles than Comparative Example 1, with Example 6 achieving 96.5%, on par with Example 3. Example 7 exhibited slightly lower ion transport efficiency due to its porous internal structure and smaller pore size, resulting in a slight decrease in cycle retention. Example 6, with its moderate pore size, achieved a balance between structural stability and ion transport, resulting in optimal cycle performance.

[0140] The carbon materials prepared in Examples 8-10 using different fluctuating curing temperatures all exhibited excellent 500-cycle retention rates in the full cells assembled from the corresponding silicon-carbon materials, which were basically equivalent to those in Example 3.

[0141] The D1 / R1 value of Comparative Example 2 is too low, resulting in too much loose region and good rate performance, but at the same time there are more defects, which leads to unsatisfactory cycle performance; the D1 / R1 value of Comparative Example 3 is too high, resulting in too little loose region and poor rate performance, which leads to unsatisfactory cycle performance.

[0142] The loose pore size of Comparative Example 4 is too large, resulting in low carbon skeleton strength and limited silicon expansion, leading to poor cycle performance; the loose pore size of Comparative Example 5 is too small, resulting in poor rate performance.

[0143] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A carbon material, characterized in that, The carbon material is in the form of spherical particles, which consist of a loose core and a dense shell from the inside out. The radial thickness of the dense shell is D1, the radius of the spherical particle is R1, and the ratio of D1 to R1 is 0.05 to 0.

5. The average pore size of the loose core is larger than that of the dense shell, and the average pore size of the loose core is 10 to 50 nm. The average pore size of the dense shell is less than 10 nm.

2. The carbon material according to claim 1, characterized in that, When the spherical particle is cut radially, the cross-section consists of a loose core and a dense shell from the inside out. When the cross-section is observed with a scanning electron microscope, the interface where the carbon skeleton changes from a dense structure without obvious pores to a loose porous structure is used as the boundary between the loose core and the dense shell.

3. The carbon material according to claim 1 or 2, characterized in that, Within the region of the loose core, there are pores with a diameter of 10~50nm in any circular region with a diameter of 0.1D0, where D0 is the equivalent diameter of the spherical particle. And / or, the D1 / R1 is 0.05~0.

2.

4. The carbon material according to claim 1, characterized in that, The carbon material has at least one of the characteristics of A1 to A3: A1. The pore volume of the carbon material is 0.2~1.5 cm. 3 / g; A2. The median particle size Dv50 of the carbon material is 2~30μm; A3. The particle size distribution of the carbon material is 0.2~1.

5.

5. A method for preparing a carbon material, characterized in that, Includes the following steps: S1. Preparation of oil and aqueous phases: The resin monomer, catalyst and additives are mixed evenly to obtain the oil phase; the dispersant and water are mixed evenly to obtain the aqueous phase; S2. Suspension preparation: At a set rotation speed, the oil phase is added dropwise to the aqueous phase, and the temperature is raised to the reaction temperature to carry out suspension emulsion polymerization, thereby obtaining a suspension containing prepolymerized microspheres; S3. Precursor synthesis: The suspension containing prepolymerized microspheres is subjected to wave solidification, and the precursor is obtained after solid-liquid separation; wherein: the wave solidification process is as follows: solidify at 80~150℃ for 1~5 min, and then solidify at 20~50℃ for 1~5 min; the wave solidification process is repeated 5~65 times. S4. Preparation of carbon materials: The precursor is carbonized and then activated in an atmosphere containing an activating gas to obtain carbon materials.

6. The method for preparing the carbon material according to claim 5, characterized in that, In step S1, the resin monomer is one of the following: phenolic resin monomer, urea-formaldehyde resin monomer, epoxy resin monomer, and styrene. And / or, the catalyst is one of hydrochloric acid, oxalic acid, sodium hydroxide, ammonia, ammonium chloride, formic acid, phosphoric acid, triethylamine, benzyl dimethylamine, benzoyl peroxide, and azobisisobutyronitrile; And / or, the additive is one or more of hexamethylenetetramine, toluene, n-heptane, ethylenediamine, diethylenetriamine, polyamide, divinylbenzene, and melamine; And / or, the dispersant is one or more of polyvinyl alcohol, gelatin, sodium carboxymethyl cellulose, sodium dodecyl sulfonate, hydroxyethyl cellulose, and calcium phosphate.

7. The method for preparing the carbon material according to claim 5, characterized in that, In step S2, the rotation speed is 100~800 rpm, the reaction temperature is 80~150℃, and the suspension emulsion polymerization time is 20~120 min; And / or, in step S3, the number of cycles is 10 to 40; And / or, in step S4, the carbonization temperature is 500~800℃, the carbonization atmosphere is one or more of nitrogen and argon; the activation gas is one or two of H2O and CO2; and the activation temperature is 700~1000℃.

8. A silicon-carbon material, characterized in that, The invention comprises carbon material and silicon particles deposited within and / or on the surface of the carbon material pores; the carbon material is the carbon material according to any one of claims 1 to 4, or the carbon material prepared by the method according to any one of claims 5 to 7; the silicon particles are obtained by chemical vapor deposition on the carbon material using a silicon-containing precursor.

9. A negative electrode, characterized in that, The negative electrode contains a negative electrode active material, which is the silicon-carbon material as described in claim 8.

10. A battery, characterized in that, The battery comprises the negative electrode as described in claim 9.

Citation Information

Patent Citations

  • Gradient-structure porous carbon, preparation method thereof and application of gradient-structure porous carbon in lithium ion battery negative electrode

    CN121757843A

  • Near-zero-expansion silicon-carbon negative electrode material and preparation method and application thereof

    CN122224816A